Crises das Idades - os entraves nas práticas docentes e as implicações no desenvolvimento da criança : uma leitura a partir de Vygotski - Caram, Adriana Maria (Universidade Federal de São Carlos, 2009)
The proposal of the present work is based on a deeper theoretical analysis of the studies by Vygotsky concerning the Age Crisis, dealt it in volume IV of his works. The manifestation of crises has always been seen as a deviation of standard norms or as a disease in preschool institutions and by some psychologists. This research has attempted to discuss another perspective in the analysis of the Age Crisis, understood by Vygotsky as being turning points in the development of a child, characterized by sudden, impetuous changes, as if they were revolutionary acts, both because of the rhythm of change and their meaning. The research question that guided our work was: How do preschool educators perceive and deal with the moments of crises in the development of children? The three objectives are: analyzing how the teachers perceive the moments of crises in the development of children; identifying and analyzing possible moments of crises among the children and researching and analyzing the attitudes taken by the teachers to solve the possible development crises in children. Data collection was carried out at a crèche in a public university in the state of São Paulo. The research method was based on Vygotsky s Historical-Cultural Theory. The results were analyzed in two different ways: The teachers perception concerning the Age Crisis in Preschool Education and its manifestation in children and The teachers and their interventions in the moments of crises. Such analyses indicate that the teachers notice the crises manifestations that occur in the development of the child. However, there seems to be a gap in their training that prevent them from perceiving such crises in a positive way, which is necessary for a new psychological organization of the child s personality. Finally, the way educators act has to be re-thought so that it is possible to adopt a reflexive pedagogical practice, based on the Historical-Cultural Theory, which understands the child as a concrete subject who participates and makes history happen.
Keywords: Educação infantil; Desenvolvimento infantil; Teoria histórico-cultural; Crise (Psicologia); Vigotsky, Lev Semenovich, 1896-1934; Crise das idades; Age crises; Preschool education; Historical-cultural theory; CIENCIAS HUMANAS::EDUCACAO